Sustainable entrepreneurship, innovation, and business models: Integrative framework and propositions for future research - Florian Lüdeke-Freund (Business Strategy and the Environment, 2019)
This article introduces the business models for sustainability innovation (BMfSI) framework to study how business models mediate between sustainability innovations and business cases for sustainability. The BMfSI framework integrates two major perspectives (implicitly) found in the sustainable business model literature. The first is the agency perspective. It takes into consideration that some form of agency is needed, that is, “someone” who takes decisions and acts. Sustainable entrepreneurs are discussed as those agents who align their new or existing business models with sustainability innovations in order to be successful in business and to create value with and for stakeholders. The second perspective is the systems perspective, which acknowledges that business models are always embedded within sociotechnical contexts through which, for example, public policies, private financing, or stakeholder interests influence whether and how business models can be developed. The agency and systems perspectives are integrated in the so-called business model mediation space. This theoretical notion embraces the decisions and activities pursued by sustainable entrepreneurs as they align their business models with sustainability innovations on the one hand and the influence of environmental contingencies, barriers, and stakeholders from the sociotechnical context on the other hand. The paper concludes with propositions for future research derived from the BMfSI framework.
Keywords: 330; sustainable entrepreneurship; business model; sustainability innovation; sociotechnical context; stakeholders; sustainable value creation; innovation theory; framework